Skrining fitokimia, formulasi dan uji mutu fisik nanoserum ekstrak bonggol nanas (Ananas comosus (L.) Merr) - Rahma Maulidia Fitri; Minda Sari Lubis; Gabena Indrayani Dalimunthe; Rafita Yuniarti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Nanoserum is a slightly viscous transparent or semi-transparent preparation whose particle size is smaller than conventional serum. The purpose of this study was to find out that pineapple hump extract contains secondary metabolites, has physical quality and has a good level of stability in the form of nanoserum. The method used in this research is experimental, the sample used is pineapple hump. The data collected is in the form of quantitative and qualitative. The results showed that pineapple hump extract contains secondary metabolites of alkaloids, flavonoids, tannins, saponins, steroids, glycosides. Organoleptic test all formulas have a clear and transparent color. In the particle size and polydispersibility index tests (F0), (F1), (F2), (F3), all formulas showing particle size and polydispersibility index met the requirements of <1000 nm and polydispersibility index <0.5. Percent transmittance test (F0), (F1), (F2), (F3), all formulas have clear and transparent visual appearance according to the requirements of 90%-100%. There was no change in the stability level of nanoserum in the organoleptic test, the particle size test and the polydispersibility index (F0), (F1), (F2), (F3). There is a change in particle size and polydispersibility index afterCyling test, however, it is still categorized as good because it is in the range of quality requirements, namely <1000 nm and the polydispersibility index <0.5.